2008
DOI: 10.2337/dc07-2118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Disease Management on Utilization and Adherence With Drugs and Tests

Abstract: OBJECTIVE -The purpose of this study was to evaluate the effect of telephonic care management within a diabetes disease management program on adherence to treatment with hypoglycemic agents, ACE inhibitors (ACEIs), angiotensin receptor blockers (ARBs), statins, and recommended laboratory tests in a Medicaid population.RESEARCH DESIGN AND METHODS -A total of 2,598 patients with diabetes enrolled for at least 2 years in Florida: A Healthy State (FAHS), a large Medicaid disease management program, who received in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Of those that did, half indicated that statins were prescribed for secondary CVD prevention [ 20 22 , 25 , 33 , 44 46 , 48 ]. Other indications included primary hypercholesterolemia [ 35 ], diabetes [ 28 , 32 ] and elevated CVD risk [ 36 , 37 , 39 , 51 ]. Five studies selected patients based on poor adherence to statin therapy [ 24 , 26 , 31 , 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of those that did, half indicated that statins were prescribed for secondary CVD prevention [ 20 22 , 25 , 33 , 44 46 , 48 ]. Other indications included primary hypercholesterolemia [ 35 ], diabetes [ 28 , 32 ] and elevated CVD risk [ 36 , 37 , 39 , 51 ]. Five studies selected patients based on poor adherence to statin therapy [ 24 , 26 , 31 , 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…: 47 vs. 15 % ( p < 0.001) Proportion receiving new statin prescriptions by 4 mo. : 55 vs. 20 % ( p < 0.001) Mean change in LDL-C (mg/dL): −12.4 vs. 6.3 ( p = 0.059) [ 25 ] Peng et al (2014) Cluster RCT 47 hospitals randomized to intervention or control group Secondary CVD prevention (China) Int: 1795 Con: 2026 61.5 ± 11.5 60.4 ± 11.7 33 31 12 1E (unique password-protected website) Proportion of adherent patients (not defined): 56 vs. 33 % ( p = 0.006) NA NA [ 26 ] Pringle et al (2014) Patients were own controls Non-adherent to statins (USA) Int: 29,042 Con: 30,454 59 60 57 55 12 2A(M) Mean PDC: 0.66 (before int) vs. 0.73 (after int) ( p < 0.001) Change from baseline in proportion with PDC ≥0.80: 7 vs. 2 % ( p < 0.001) NA NA [ 27 ] Taitel et al (2012) Retrospective; Unmatched controls; Statistical analysis adjusted for co-variates Statin naïve (USA) Int: 586 Con: 516 54.2 ± 12.4 56.0 ± 12.2 54 51 12 2A(M) Mean MPR: 0.62 vs. 0.57 ( p < 0.01) Proportion with MPR ≥0.80: 40.9 vs. 33.7 % ( p < 0.01) Proportion persistent (<60 consecutive days without any statin medication available): 43.9 vs. 38.2 % ( p = 0.05) NA [ 28 ] Thiebaud et al (2008) Prospective; Matched controls Diabetes (USA) Int...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in adherence have been shown to result from several types of interventions including policy interventions, telephonic and text message follow‐up, as well as educational interventions by pharmacists . The effect size and sustainability of these impacts on adherence and subsequent patient outcomes, however, have been somewhat modest.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, disease management (DM) programs are being conducted telephonically 115–120 . Telephone DM counseling has been used to address a wide range of health issues including medication adherence 121,122 , diabetes control 123127 , heart failure 120,122,128 , smoking cessation 129 , and adult weight management 130136 . Many health care delivery systems including the Veterans Administration 126,131,137 , integrative health care delivery systems 129,138,139 , and both Medicare and Medicaid 121124,140 use DM to manage chronic disease, and this approach appears to be increasingly utilized across the health care delivery system 139,140 .…”
Section: Discussion and Future Enhancements To Bmi2mentioning
confidence: 99%